Space Debris Debate; Implementation of Socio-Scientific Issues in Science Learning to Improve Argumentation Skills - Ainun Ilmi Wahidah; Supeno Supeno; Bea Hana Siswati (FKIP Universitas Lampung, 2024)
Space Debris Debate; Implementation of Socio-Scientific Issues in Science Learning to Improve Argumentation Skills. Objectives: This study aims to assess the impact of implementing science learning with a socio-scientific issue approach and debate on space debris on scientific argumentation skills. Methods: The type of research applied was a quasi-experiment using a non-equivalent control group design. In the experimental class, learning science with debate activities on space debris within the socio-scientific issue framework was applied for four lessons, while in the control class, the usual learning was carried out by the teacher. The test data was analyzed using a t-test to determine whether the treatment had an impact on argumentation skills. Findings: Implementation of science learning with a socio-scientific issue approach and debate activities on space debris had a significant impact on scientific argumentation skills. Students defend their argument from other rebuttals by showing scientific evidence and providing scientific explanations. Conclusion: Science debate about space debris in science learning with a socio-scientific issue approach can provide a dynamic learning experience, students can provide claims accompanied by scientific evidence and reasoning that connects claims with evidence. Keywords: science debate, socio-scientific issue, space debris, argumentation skills.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202482